Peran Identitas Kependudukan Digital (IKD) dalam Meningkatkan Kualitas Layanan Publik yang Cepat dan Mudah di Dinas Kependudukan dan Pencatatan Sipil Kota Bukittinggi - Anisa Humdiah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study discusses the implementation of Digital Population Identity (IKD) as an innovation in public services at the Population and Civil Registration Office (Disdukcapil) in Bukittinggi City. IKD, as an application-based population identity system, in accordance with Minister of Home Affairs Regulation Number 72 of 2022, combines the e-KTP (electronic ID card) and other resident documents in digital form. This research employed a descriptive method, using a case study approach that included interviews, observations, and analysis of supporting documents. The findings indicate that IKD can accelerate and facilitate access to public services, improve administrative efficiency, and provide data security through a biometric authentication system. However, several challenges remain in the implementation of IKD, such as a lack of public awareness, low digital literacy among the public, limited smartphone availability, and network issues with the Population Administration Information System (SIAK). With the support of appropriate infrastructure and increased digital literacy, IKD has the potential to become a model for effective, efficient, and accessible digital public services, and can be implemented in other regions of Indonesia.